Social Skills and Suicide Risk in Adolescents of an Education Institute of the City of Armenia (Quindío, Colombia) (2019)
Introduction: The objective of this article is to establish the relationship between the acquisition of social skills and the clinical expression of suicidal ideation and suicide risk in adolescents. Materials and Methods: The research was conducted following a descriptive and correlational design, in a population of 115 adolescents aged between 12 and 18 years old. The Beck's Hopelessness Scale and the Goldstein Social Skills Test were applied. Results: Data showed that there is a significant, inversely proportional correlation between the social skills and a lower risk of suicidal symptomatology. Conclusion: Based on the obtained results it was possible to corroborate how family plays a relevant role in the emotional regulation and in acquiring social skills in the individual, it was also possible to sustain that, on the basis of a healthy copying style in the resolution of vital problems, the possibility of developing any suicidal expression slows down.